2021
DOI: 10.1080/23311975.2021.1935185
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual formation and explanation in IFRS-based financial accounting research

Abstract: This article provides a comprehensive review of the conceptual formation and explanation within International Financial Reporting Standards (IFRS)-based financial accounting research. The mandatory adoption of IFRS by the European Union (EU) on 1 January 2005 resulted in an increase in the number of scientific articles explaining the effect of mandating IFRS on capital markets within the EU. Independently, these studies offer interesting insights; however, there have been few attempts to offer a critical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…The study concluded that adopting IFRS standards is a possible factor that can improve value relevance. Likewise, Kainth and Mustafa (2021) reviewed IFRS-based financial accounting comprehensively. They suggested that most articles reviewed are more likely to be borrowed from the mainstream and finance literature used in irregular forms.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…The study concluded that adopting IFRS standards is a possible factor that can improve value relevance. Likewise, Kainth and Mustafa (2021) reviewed IFRS-based financial accounting comprehensively. They suggested that most articles reviewed are more likely to be borrowed from the mainstream and finance literature used in irregular forms.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%